Steps to become a professional engineer in Malaysia - Wan Sharuzi, Wan Harun; Mohd Fairusham, Ghazali; Norazlianie, Sazali; Mohamad Huzaimy, Jusoh; Shahrul Niza, Mokhatar (Penerbit UMPSA, 2023)
The book presents systematic guidelines for becoming a professional engineer (PEng) through the Institution of Engineers Malaysia (IEM) Route C (Corporate Member of IEM). The book 'Professional Engineer: A Step-by-step guide' is dedicated to engineers who aim to successfully apply to professional engineers in Malaysia. The content is comprehensive and covers application submission through Route C until registration as a professional engineer with the Board of Engineers Malaysia (BEM).